The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3889/oamjms.2021.7065
|View full text |Cite
|
Sign up to set email alerts
|

The Avocado (Persea americana Mill.) Leaf Extract on Streptozotocin-induced Pancreatic Cell Regeneration of White Rats (Rattus norvegicus)

Abstract: Objectibe The rate of pancreatic cell regeneration after avocado leaf extract intervention in a diabetic animal model induced by streptozotocin was investigated in this study. Method: Experimental study was conducted on 18 male white rats as subjects, which were divided into 6 groups, 3 animals of each. Those were G1 (Feed + Streptozotocin + 10% Sucrose + 100 mg/kg b.w. of extract + 0.5% NaCMC), G2 (Feed + Streptozotocin + 10% Sucrose + 150 mg/kg b.w. of extract + 0.5% NaCMC), G3 (Feed + Streptozotocin + 10% S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
0
0
0
Order By: Relevance
“…Increasing the dose of avocado extract seems to increase the regenerative effect on the pancreas. However, the most severe cell damage was seen in the group that received 0.5% Na-CMC vehicle (Rahman et al, 2021). This suggests that avocado ethanolic extract can enhance pancreatic cell regeneration and be a potential candidate as a regenerative agent in conditions of pancreatic cell damage.…”
Section: Avocado Fruit Peel Extract and Antidiabeticmentioning
confidence: 93%
See 1 more Smart Citation
“…Increasing the dose of avocado extract seems to increase the regenerative effect on the pancreas. However, the most severe cell damage was seen in the group that received 0.5% Na-CMC vehicle (Rahman et al, 2021). This suggests that avocado ethanolic extract can enhance pancreatic cell regeneration and be a potential candidate as a regenerative agent in conditions of pancreatic cell damage.…”
Section: Avocado Fruit Peel Extract and Antidiabeticmentioning
confidence: 93%
“…Follow-up research conducted by Rahman et al (2020) showed that avocado leaf extract has the potential to increase kidney cell regeneration in male white rats with diabetes (Rahman et al, 2022). The results showed that the dose of avocado leaf extract affected the level of kidney damage, where the higher the dose of the extract given, the lower the level of kidney damage that occurred.…”
Section: Avocado Fruit Peel Extract and Antidiabeticmentioning
confidence: 99%